A six-step brief intervention to reduce distress and increase treatment readiness in problem gamblers. (August 2020) - Oakes, Jane E; Manning, Victoria; Rodda, Simone N; Lubman, Dan I
Objective: The majority of people with gambling problems contact helplines when they are in crisis, hampering their capacity to explore suitable treatment options. To date, there has been limited research identifying the best way to support individuals to reduce distress and maximise further treatment-seeking. In this paper, we describe the development and piloting of the resulting six-step brief intervention. Method: A six-step brief intervention was developed based on a literature review of existing interventions for crisis management, semi-structured interviews with 19 participants comprising gambling and crisis support counsellors and consumers, as well as experts in the addiction field. Results: The resulting six-step brief-intervention focusses on (1) acknowledging and measuring distress; (2) normalising and reducing distress; (3) optimising motivation for change; (4) providing a sense of hope; (5) re-measuring distress and, if reduced; (6) exploring options for treatment and support. Conclusion: Whilst developed primarily for helpline counsellors, the intervention has potential application for health practitioners working across telephone, online and face-to-face services. Further research is required to determine its effectiveness in improving treatment engagement amongst people with gambling problems.